DOMESTIC CAT (Felis catus) AS A TRANSMISSION LINK FOR DERMATOPHYTOSIS BY Microsporum canis TO HUMANS– CASE REPORT - FEITOSA, LAURO CESAR; Brasileiro, Caio Barbosa; Ferreira, Siluana Benvindo; Diniz, Bruno Leandro Maranhão; Alcantara, Diana Sousa; Tenório, Taciana Galba da Silva; Tenório, Taciana Galba da Silva (Revista de Ciência Veterinária e Saúde Pública, 2020)
Microsporum canis, a species considered to be zoophilic, is referred to as the mains causative agente of dermatophytosis, being the one that has the highest occurrence in dogs and cats, as well as the main agente responsible for zoophilic dermatophytic infections in humans. The objective of this work was to report a case of familial microepidemic by M. canis in the city of Teresina, Piauí.